2014
DOI: 10.12944/carj.2.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Status of Cambo dian Soils, Rationalisation of Fertiliser Recommendations and the Challenges Ahead for Cambodian Soil Science

Abstract: Soils of Cambodia are low in fertility and conventional rice cultivation destroys any structure that they have. Usage of inorganic fertilizers is low and farmers are encouraged to use animal manure. Much of the research conducted on crop responses to manure is based on trials where unrealistically high application rates have been used so the farmers are given false hopes as to what they might achieve through its use. Little response curve data exists on which to base fertilizer rate recommendations and general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Interestingly, the yield response to K input combined with N input was also significant on the Toul Samroung soil, except at Battambang in 2016 ( Figure 2). Previous studies suggested a low requirement for supplemental K on the Toul Samroung soil, since the soil is already relatively rich in plant-available K (Table 1; Blair and Blair, 2014;Oberthur et al, 2000;White et al, 2000). It is likely that long-term intensive use of N and P fertilizers on this fertile soil leads to increased K uptake by plants, thereby gradually depleting the available K in many fields (Seng et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Interestingly, the yield response to K input combined with N input was also significant on the Toul Samroung soil, except at Battambang in 2016 ( Figure 2). Previous studies suggested a low requirement for supplemental K on the Toul Samroung soil, since the soil is already relatively rich in plant-available K (Table 1; Blair and Blair, 2014;Oberthur et al, 2000;White et al, 2000). It is likely that long-term intensive use of N and P fertilizers on this fertile soil leads to increased K uptake by plants, thereby gradually depleting the available K in many fields (Seng et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…The low soil fertility results from weathering of soils with a low carbon content, as is typically seen in the Prateah Lang and Prey Khmer soil groups, which cover 25-30% and 10-12%, respectively, of the country's rice-growing area (White et al, 2000). Blair and Blair (2014) estimated that 87% of the country's soils have less than 10 g kg −1 of organic carbon content. Coarse-textured soils respond poorly to nutrient management owing to their low nutrient-holding capacity (Haefele et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of field studies have focused on the improvement of nutrient management of wet-season rice in Cambodia to close the nationwide yield gap, that is, increasing mean farm yield (3.3 t ha −1 ; MAFF, 2018) towards potential yield (Blair and Blair, 2014;Seng et al, 2001;Wade et al, 1999;White et al, 2000). Potential yield is the yield of a cultivar grown in environments to which it is adapted with non-limiting water and nutrient conditions (Evans and Fischer, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The main production area is characterized by highly weathered sandy Fluvisols with low organic matter and N contents ( Seng et al, 2001), extremely low available P contents, and low‐activity material dominating the clay fraction ( White et al, 1997). Mineral fertilizer sources are often unaffordable to small‐scale producers ( Blair and Blair , 2014), the efficiency of recommended application rates is highly variable, and profitability is often low ( Seng et al, 2001), possibly the result of leaching losses of nutrients other than P. Only low amounts of farmyard manure (FYM) are generally applied due to the limited number of farm animals.…”
Section: Introductionmentioning
confidence: 99%